The Relationship of Nutritional Status and Energy Adequacy with the Work Productivity of Class I Kedungpane Semarang Penitentiary Employees - Nabila, Firda Ainun; Susilowati, Fitria; Octavia, Zana Fitriana (Universitas Negeri Medan, 2024)
Employee productivity is very important for a company. Employees who have good productivity will produce high-quality products or services. Nutritional status and energy adequacy are one of the factors that affect employee productivity. Energy intake will be the main source of energy for employees to do work. The more adequate energy intake will make the nutritional status close to normal. Determine the relationship between nutritional status and energy adequacy with the work productivity of employees of Class I Correctional Institution Kedungpane Semarang. This type of research uses observational analytics with a cross sectional approach. This research was conducted at the Class I Penitentiary Kedungpane Semarang. The sampling technique is consecutive sampling of 70 employees. The data measured are nutritional status with anthropometric measurements consisting of employee weight and height, energy adequacy with a 3x24 hour food recall instrument, and work productivity using a 3-day work time record. The results of bivariate tests using the Gamma test showed that there was a relationship between nutritional status and work productivity (p = 0.000), and there was a relationship between energy adequacy and work productivity (p = 0.024). There is a relationship between nutritional status and energy adequacy with the work productivity of Class I Kedungpane Semarang Penitentiary employees.